Colombia : Request for Augmentation of Access Under the Flexible Credit Line Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Colombia. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
The current FCL arrangement for Colombia was approved in May 2020. Colombia was cited for its very strong policy frameworks-anchored by a flexible exchange rate, a credible inflation-targeting regime, effective financial sector supervision and regulation, and a structural fiscal rule-and a track record of very strong policy implementation that served as a basis for the economy's resilience prior to the Covid-19 pandemic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet